Transformation of Broca’s Aphasia into Conduction Aphasia: A Case Report - S. Kazui; T. Sawada; H. Tanabe; N. Inoue (Behavioural Neurology)
We describe a patient with a cerebral infarction localized mainly in the left posterior frontal and anterior parietal subcortices who experienced a Broca's aphasia which evolved into a conduction aphasia. Such a rare recovery pattern of aphasia appeared to result from amelioration of the damage to the left precentral gyrus.